Enhancing EFL Speaking Skills Through Thematic Comic Strips: An Exploration in a Junior High School Setting - Munir Munir; Sudarwinoto Sudarwinoto; Suhesty Suhesty; Suriama Yaman (Pascasarjana Universitas Negeri Makassar, 2023)
This study investigates the novel application of comic strips as a pedagogical tool to enhance speaking skills among EFL students in a junior high school setting, with a thematic focus on